2020
DOI: 10.1177/0033294120937441
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Effectiveness of a Strengths-Based Intervention Targeting All 24 Strengths: Results From a Randomized Controlled Trial

Abstract: This study assessed the effectiveness of a strengths-based randomized controlled trial focused on fostering all 24 character strengths in a group of 75 participants from a University in Tunisia. Participants randomly assigned to the challenge condition (n = 40) received an email each day for 24 days, that highlighted a particular strength of the day including why the strength is valuable, how to implement the strength behaviourally, and a motto related to that strength. Those in the control condition (n = 35) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
0
3
0
2
Order By: Relevance
“…Two RCTs (Basurrah et al, 2020; Chérif et al, 2021) examined the effects of character strengths. Chérif et al's (2021) study focused on fostering all 24‐character strengths over 24 days in university students ( n = 75). There was no difference between the two groups on happiness immediately following the intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Two RCTs (Basurrah et al, 2020; Chérif et al, 2021) examined the effects of character strengths. Chérif et al's (2021) study focused on fostering all 24‐character strengths over 24 days in university students ( n = 75). There was no difference between the two groups on happiness immediately following the intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the results of a recent pilot study found positive impacts on enhancing emotional regulation and reducing stress among Arab teachers (Berkovich-Ohana et al, 2020 ). Some studies have also begun to examine various interventions targeting character strengths (Basurrah et al, 2020 ; Chérif et al, 2021 ), self-compassion (Elaiwah, 2017 ), positive thinking (Haddad, 2014 ; Mohammed et al, 2014 ), and hope (Zaki, 2016 ) among adults and university students. Interestingly, a recent study by Lambert et al ( 2019 ) has examined the impact of PPIs on fear of happiness (a belief that happiness or positive emotions can bring forward negative consequences; Joshanloo, 2013 ) among people from collective countries.…”
Section: Positive Psychology In the Arab Regionmentioning
confidence: 99%
“…Az erősségek birtoklása és használata, és az olyan életmód folytatása, amit az erények mint iránytűk vezetnek, a pozitív mentális egészség markerei (Oláh & Kapitány-Fövény, 2012). Aki az erényei szerint él, az boldog és kiegyensúlyozott (Cherif, Wood, & Watier, 2020;Gander, Hofmann, Proyer, & Ruch 2019;Lee és mtsai, 2020;Niemiec & McGrath, 2019). Az eredeti mérőeszköznek (Peterson & Seligman, 2004) már 14 kultúrközi adaptációja elérhető (VIA, 2022).…”
Section: Bevezetésunclassified